1995
DOI: 10.1029/94jd01943
|View full text |Cite
|
Sign up to set email alerts
|

Radio interferometric observations of cloud‐to‐ground lightning phenomena in Florida

Abstract: Radio frequency observations of cloud‐to‐ground lightning in Florida have been analyzed to document a number of features of the lightning. The observations have been made using an interferometer system which determined the direction to the lightning radiation as a function of time during close lightning discharges. Observations are presented for about 50 radiating events during five multiple‐stroke, normal‐polarity flashes to ground. The results confirm and extend results of a similar study of New Mexico light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
270
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 242 publications
(313 citation statements)
references
References 25 publications
40
270
3
Order By: Relevance
“…It has been previously been observed that detectable HF and VHF radiation from thunderstorms is produced primarily by breakdown processes and not by charge flow along already conducting channels [Rhodes et al, 1994;Shao et al, 1995]. This result is exemplified by the absence of detectable RF radiation during the initial parts of return strokes initiated by dart leaders and during long intervals of continuing current discharges to ground.…”
Section: Cid Size Charge and Currentsupporting
confidence: 49%
See 2 more Smart Citations
“…It has been previously been observed that detectable HF and VHF radiation from thunderstorms is produced primarily by breakdown processes and not by charge flow along already conducting channels [Rhodes et al, 1994;Shao et al, 1995]. This result is exemplified by the absence of detectable RF radiation during the initial parts of return strokes initiated by dart leaders and during long intervals of continuing current discharges to ground.…”
Section: Cid Size Charge and Currentsupporting
confidence: 49%
“…Based on their results and the fact that the RF radiation from CIDS is very powerful (20 dB brighter than that produced by other lightning breakdown processes), it might be concluded that the strongly radiating part of the streamer results from negative breakdown progressing in an upward direction and transporting negative charge upward. On the other hand, it was also concluded by Shao et al [1995] that positive breakdown that produces a conducting channel is difficult to initiate. As will be shown shortly, electric field strengths just prior to CIDS are comparable to or greater than the highest electric fields that have been measured within thunderstorms.…”
Section: Most Measurements Of Average 2-d Ieader Velocities Have Beenmentioning
confidence: 99%
See 1 more Smart Citation
“…At each R in the diagram, a sharp change toward positive polarity was observed for several microseconds during the buildup of electric field strength; since the positive change prevails, this example presents a negative cloud-to-ground discharge with a multiplicity of 6. Regarding UHF radiation, a strong emission caused by return stroke is observed as well as a preceding emission that is related to the leader progression, which is a feature of negative cloud-to-ground strokes [3,12]. Figure 4 shows a 3D image of the lightning channel in the time region corresponding to the first leader progression marked L1 in Fig.…”
Section: Uhf Interferometric Measurement and 3dmentioning
confidence: 95%
“…When the phase difference goes through more than one cycle in a high-frequency component, there is the possibility of a fringe ambiguity [4][5][6]. We remove the ambiguity using the feature that the phase difference should be linearly dependent on frequency.…”
Section: Principle Of the Broadband Digital Interferometrymentioning
confidence: 99%